Concept and place, the Works of portuguese architect Álvaro Siza - Robles Cairo, Cuauhtémoc (UNIVERSIDAD DE SONORA, 2021)
This article presents an assessment of the first works of the portuguese architect Alvaro Siza Vieria, from the perpective of the conceptual definition of projects in relation to the characteristics of the physical context where they are located. It is also an invitation to reflect on the inherent principles to the architectural object,  such as the relationship of the building with the context . It is proposed as a starting point  the wear that is had in the student-academic enviroment  on the analogous conceptualization that evoques creative forms without a support, under the protection of individual subjectivity and creativity. The conceptual description of four emblematic buildings analyzed is presented:  the  Piscinas des mares, the Boa Nova restaurant, The Oporto's Architecture School and the Galician Center and concludes with a reflection on the architec's works and with a thematic instrument that facilitates the students to assess the specific topics  as a path towards a conceptualization linked to the place.